Race and Class beyond Enrollment: The Link between Socioeconomic Diversity and Cross-Racial Interaction. (3rd September 2019) - Park, Julie; Bowman, Nicholas; Denson, Nida; Eagan, Kevin
ABSTRACT: Colleges increasingly emphasize the importance of socioeconomic diversity, but little work examines the link between such diversity and outcomes important to the campus climate. Using a national dataset, we test the link between two measures of socioeconomic diversity and cross-racial interaction, an outcome paramount to triggering the benefits of diversity. Findings indicate that there was no direct effect associated with this form of socioeconomic diversity. However, cross-racial interaction was lowest at institutions with lower structural income diversity and lower structural racial diversity. Comparison of predictors between income groups also identify that middle and upper-income Black students have significantly higher rates of cross-racial interaction. Implications for policymakers and educators are discussed.